For Your Page TikTok: The Influence of Self-Esteem on Online Self-Presentation in Teenagers - Sari, Diah Puspita; Sa'id, Mochammad (Jurnal Sains Psikologi, 2023)
The existence of TikTok is often used to present oneself virtually. However, this virtual appearance can cause individuals to attempt to commit appearance fraud or lying self-presentation, which they believe can affect their self-esteem as the best version of themselves. This research aims to determine the influence of self-esteem on online self-presentation among adolescent users of the TikTok application in Tasikmalaya Regency. The design of this research uses a correlational quantitative approach. The sampling technique used in this research was a non-probability sampling method with an accidental sampling type and obtained a sample of 537 research subjects. This research uses two scales adapted by researchers, including the Rosenberg Self-Esteem Scale (RSES) to measure self-esteem and The Presentation of Online-Self Scale (POSS) to measure online self-presentation. The data analysis technique uses simple linear regression. This study's results show that self-esteem significantly influences online self-presentation among teenage TikTok users in Tasikmalaya Regency (t equals 27.154; p equals 0.01 less than 0.05; R2 equals 0.020). This research concludes that the lower self-esteem, the higher online self-presentation in adolescents. In this case, self-esteem contributes to online self-presentation by 2 percent.